Shadow Economy and its Impact on Tax Revenues in Mojokerto City - Lukito, Harjo; Firdaus Nurwicaksono Adi, Alifone (Profit: Jurnal Adminsitrasi Bisnis, 2023)
This study aims to empirically study the effects of the allocation, distribution, and stabilization variables on the shadow economy and their impact on tax revenues. This research is descriptive-explorative and explanatory research. The research location is at the PKL Center, Jl. Fort Pancasila City of Mojokerto. The population of 369 with the Slovin tolerance formula of 0.01 was determined as a sample of 79 respondents. Data collection uses a questionnaire; data analysis is assisted by SmartPLS software version 3.3.7. The results show: 1) Allocations have a significant effect on the shadow economy; 2) Distribution has a significant effect on the shadow economy; 3) Stabilization has no effect on the shadow economy; 4) Allocations do not affect tax revenues; 5) Distribution has a significant effect on tax revenues; 6) Stabilization has a significant effect on tax revenues; 7) Shadow economy has a significant effect on tax revenues; 8) Allocations have an indirect effect on tax revenues through the shadow economy; 9) Distribution has an indirect effect on tax revenues through the shadow economy; 10) Stabilization has an indirect effect on tax revenues through the shadow economy.